Antioxidative Properties and Acrylamide Content of Functional Wheat-Flour Cookies Enriched with Wild-Grown Fruits - Borczak, Barbara; Sikora, Marek; Kapusta-Duch, Joanna; Fołta, Maria; Szewczyk, Agnieszka; Zięć, Gabriela; Doskočil, Ivo; Leszczyńska, Teresa (Molecules (Basel, Switzerland), 2022)
This study aimed to evaluate the impact of widely grown fruits (wild roses, elderberries, sea buckthorns, rowans, chokeberries, and hawthorns) as a functional ingredient in wheat-flour cookie formulation on antioxidative properties with a simultaneous reduction of the carcinogen-like compound acrylamide. The organoleptic features of the cookies were assessed by a panel of consumers. The following parameters were measured: chemical composition, total polyphenols, polyphenolic profile, antioxidant activity, and acrylamide content. The overall ratings of the tested cookies with the addition of chokeberries, hawthorns, sea buckthorns, and elderberries were more than satisfactory, while wild rose and rowan cookies were the most widely accepted and best rated by the panelists. The antioxidant activity of the tested cookies was 1.1−15.22 μmol trolox·g−1 dm and 2.46−26.12 μmol Fe (II)·g−1 dm as measured by the ABTS and FRAP methods, respectively. All the fruit-enriched cookies had significantly higher antioxidative properties (p < 0.05) in comparison to the control cookies, but among the fruit-enriched cookies, there were differences in the quality and quantity of particular polyphenols. The acrylamide content was significantly decreased by 59% (hawthorn), 71% (rowan), 87% (wild rose), 89% (sea buckthorn), 91% (elderberry), and 94% (chokeberry) compared with the control cookies (p < 0.05). Cookies enriched with wild-grown fruits could constitute a promising novel snack food.
Keywords: Triticum; Sambucus; Acrylamide; antioxidancia; bez; Sorbus; akrylamid; polyfenoly; Flour; wild-grown fruits; pšenice; acrylamide; antioxidant properties; mouka; wheat-flour cookies; ovoce; polyphenols; Antioxidants; Fruit; Polyphenols